2020
DOI: 10.1074/jbc.ra120.014814
|View full text |Cite
|
Sign up to set email alerts
|

Ferric uptake regulator (Fur) reversibly binds a [2Fe-2S] cluster to sense intracellular iron homeostasis in Escherichia coli

Abstract: The ferric uptake regulator (Fur) is a global transcription factor that regulates intracellular iron homeostasis in bacteria. The current hypothesis states that when the intracellular “free” iron concentration is elevated, Fur binds ferrous iron and the iron-bound Fur represses the genes encoding for iron uptake systems and stimulates the genes encoding for iron storage proteins. However, the “iron-bound” Fur has never been isolated from any bacteria. Here we report that the Escherichia coli Fur has a bright r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 57 publications
(118 reference statements)
2
62
0
Order By: Relevance
“…FeSO 4 also reduced the activity of the chromosomal reporter strain CFT073 tcpC::gfpmut2 significantly after incubation of 3 h and overnight ( Figure 9 G,H). To further analyze the influence of FeSO 4 on the P2 promoter, we used the iron chelator 2,2’-bipyridine, which is also known to deplete intracellular iron from E. coli [ 22 ]. We found that incubation of the P2-reporter strain with the iron chelator significantly increased the activity of the P2 promoter ( Figure 10 ).…”
Section: Resultsmentioning
confidence: 99%
“…FeSO 4 also reduced the activity of the chromosomal reporter strain CFT073 tcpC::gfpmut2 significantly after incubation of 3 h and overnight ( Figure 9 G,H). To further analyze the influence of FeSO 4 on the P2 promoter, we used the iron chelator 2,2’-bipyridine, which is also known to deplete intracellular iron from E. coli [ 22 ]. We found that incubation of the P2-reporter strain with the iron chelator significantly increased the activity of the P2 promoter ( Figure 10 ).…”
Section: Resultsmentioning
confidence: 99%
“…The new study by Fontenot et al (5) convincingly shows that bacterial Fur proteins isolated from E. coli can bind an all-Cys-coordinated [2Fe-2S] cluster. Therefore, it seems possible that this metallo cofactor rather than the previously thought mononuclear Fe 21 may serve as the iron-regulatory device (Fig.…”
Section: Edited By Ruma Banerjeementioning
confidence: 97%
“…1b) (2,9). Finally, Fontenot et al (5) overexpressed the Fur ortholog from the Gramnegative bacterium Haemophilus influenzae in DiscA/sufA E. coli cells. This protein bound even 2-fold more [2Fe-2S] cluster, implying that cluster binding may be a general feature of Fur proteins.…”
Section: Edited By Ruma Banerjeementioning
confidence: 99%
See 1 more Smart Citation
“…The available structures of Fur proteins from different organisms unveil that, in addition to the regulatory metal-binding site, Fur displays a so-called structural zincbinding site which, in most cases, is formed by four cysteines arranged in two CXXC motifs [1]. Furthermore, it has been found that, in E. coli, Fur binds a [2Fe-2S] cluster via conserved cysteine residues [7]. Fur has also been identified as one of the transcription factors that are associated with thioredoxin in a detailed analysis of the thioredoxinlinked E. coli proteome [8], as well as in further studies using E. coli engineered strains to optimize trapping and characterization of the in vivo Trx redox interactome [9].…”
Section: Introductionmentioning
confidence: 99%